PEEK Versus Titanium Static Interbody Cages: A Comparison of 1-Year Clinical and Radiographic Outcomes for 1-Level TLIFs. Issue 8 (October 2021) - Canseco, Jose A.; Karamian, Brian A.; Patel, Parthik D.; Divi, Srikanth N.; Timmons, Tyler; Hallman, Haydn; Nachwalter, Ryan; Lee, Joseph K.; Kurd, Mark F.; Anderson, D. Greg; Rihn, Jeffrey A.; Hilibrand, Alan S.; et al.
Abstract : Study Design: This was a retrospective cohort study. Objective: This study evaluates the patient-reported Health Related Quality of Life outcomes and radiographic parameters of patients who underwent a single level transforaminal lumbar interbody fusion with either a polyetheretherketone (PEEK) or titanium interbody cage. Summary of Background Data: Spinal stenosis with instability is a common diagnosis that is often treated with interbody fusion, in particular transforaminal lumbar interbody fusion. Titanium and PEEK interbody cage properties have been extensively studied to understand their effect on fusion rates and subsidence. Materials and Methods: A retrospective cohort study was conducted from a single, high volume, academic hospital. Health Related Quality of Life outcomes were obtained from Outcomes Based Electronic Research Database and electronic medical record chart review. Subsidence was defined as a loss of 2 mm or more in the anterior or posterior disk height. Spinopelvic alignment parameters measured were sacral slope, pelvic tilt, pelvic incidence, lumbar lordosis, segmental lordosis, and pelvic incidence-lumbar lordosis mismatch. Fusion rates were assessed by the Brantigan-Steffee criteria. Results: The study included a total of 137 patients (108 PEEK, 29 titanium). Overall, no significant changes were noted between the 2 groups at 3 month or 1-year follow-up. Perioperatively, patients did report improvement in all outcome parameters within the PEEK and titanium groups. No significant difference was noted in subsidence rate between the 2 groups. Segmental lordosis significantly increased within the PEEK (+4.8 degrees; P <0.001) and titanium (+4.6 degrees; P =0.003) cage groups, however no difference was noted between groups. No significant difference was noted in fusion between the PEEK and titanium cage cohorts (92.6% vs. 86.2%; P =0.36). Conclusion: Overall, while PEEK and titanium cages exhibit unique biomaterial properties, our study shows that there were no significant differences with respect to patient-reported outcomes or radiographic outcomes between the 2 groups at the 1-year follow-up time point. Level of Evidence: Level III.